Si‐Encapsulating Hollow Carbon Electrodes via Electroless Etching for Lithium‐Ion Batteries. Issue 2 (7th September 2012) - Park, Yuwon; Choi, Nam‐Soon; Park, Sangjin; Woo, Seung Hee; Sim, Soojin; Jang, Bo Yun; Oh, Seung M.; Park, Soojin; Cho, Jaephil; Lee, Kyu Tae
Abstract Remarkable improvements in the electrochemical performance of Si materials for Li‐ion batteries have been recently achieved, but the inherent volume change of Si still induces electrode expansion and external cell deformation. Here, the void structure in Si‐encapsulating hollow carbons is optimized in order to minimize the volume expansion of Si‐based anodes and improve electrochemical performance. When compared to chemical etching, the hollow structure is achieved via electroless etching is more advanced due to the improved electrical contact between carbon and Si. Despite the very thick electrodes (30 ∼ 40 μm), this results in better cycle and rate performances including little capacity fading over 50 cycles and 1100 mA h g−1 at 2C rate. Also, an in situ dilatometer technique is used to perform a comprehensive study of electrode thickness change, and Si‐encapsulating hollow carbon mitigates the volume change of electrodes by adoption of void space, resulting in a small volume increase of 18% after full lithiation corresponding with a reversible capacity of about 2000 mA h g−1.